2023
DOI: 10.1111/ijd.16688
|View full text |Cite
|
Sign up to set email alerts
|

Surgical margin mapping for lentigo maligna and lentigo maligna melanoma: traditional technique (visual inspection with dermoscopy) versus combined paper tape and reflectance confocal microscopy technique

Abstract: Background The detection of subclinical margin in lentigo maligna/lentigo maligna melanoma (LM/LMM) can be challenging for the dermatologist. Reflectance confocal microscopy (RCM) enables to observe in vivo atypical melanocytes beyond the clinical margins. The aim of this study is to establish which of these methods (clinical examination and dermoscopy versus “Paper tape – RCM”) is more precise to define the lesion margin and to reduce the number of re‐intervention and overtreatments in cosmetically sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…In the last few years, reflectance confocal microscopy (RCM), a non-invasive imaging technique that proved to be more sensitive and specific than dermoscopy in the diagnosis of LM, was studied in detecting the margins and reducing the risk of positive margins. Studies showed that RCM reduces the rate of positive histological margins, reduces the number of necessary stages, leading to less local recurrences [18,26,27]. When margin-controlled surgery is not available, RCM is associated with a better demarcation of the lesion, avoiding incomplete excision.…”
Section: Surgical Margin Mapping For Lmmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, reflectance confocal microscopy (RCM), a non-invasive imaging technique that proved to be more sensitive and specific than dermoscopy in the diagnosis of LM, was studied in detecting the margins and reducing the risk of positive margins. Studies showed that RCM reduces the rate of positive histological margins, reduces the number of necessary stages, leading to less local recurrences [18,26,27]. When margin-controlled surgery is not available, RCM is associated with a better demarcation of the lesion, avoiding incomplete excision.…”
Section: Surgical Margin Mapping For Lmmentioning
confidence: 99%
“…When margin-controlled surgery is not available, RCM is associated with a better demarcation of the lesion, avoiding incomplete excision. Moreover, even when margin-controlled surgery is available, the use of RCM leads to more precise and efficient surgical management of the lesion [18,26,27].…”
Section: Surgical Margin Mapping For Lmmentioning
confidence: 99%